FACTORS of PRODUCTION RICE CORPORATE FARMING MODEL in CENTRAL JAVA - Dwi Haryati Ningsih; Muhammad Joni Iskandar; Elwani Hidayati (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2022)
The agricultural sector is still faced with various problems. Starting from the increasingly narrow land, decreased land productivity due to the use of inappropriate production factors, erratic and unpredictable climatic conditions to the issue of unique prices that fluctuate at any time. These obstacles and constraints will ultimately affect the income of farmers. The distribution of income is obtained from the production and productivity of rice farming during the growing season. Increased production can be done through the agricultural model of corporate farming. This study aims to estimate the factors that influence rice production with the corporate farming model. The research location was determined purposively in Sukoharjo Regency. Sampling by census was 51 corporate farmers. Estimated data to produce factors of production using the Cobb-Douglass production function model. The results showed that the factors that significantly affected the increase in rice production using the corporate farming model were land area and urea fertilizer. Meanwhile, the production factors of SP-36 fertilizer, NPK fertilizer, pesticides and labor did not have an effect on the increase in rice production so that these production factors could be an opportunity to improve production and productivity.